Effect of the RME Biodiesel on the Diesel Engine Fuel Consumption and Emission - Dariusz Kurczyński (Communications - Scientific letters of the University of Zilina, 2021)
Road transport is the primary source of atmospheric air pollution, thus posing a threat to human health and life. The aim of the study was to determine the impact of fuel obtained from plants on the ecological properties of a compression ignition engine. The article reports the results of investigations into a modern engine with a Common Rail system, powered by the RME (rapeseed methyl esters) biodiesel and their blends with diesel. For comparison, the engine was also fuelled with conventional diesel oil without ester addition. When powering the engine with blends and pure biodiesel, brake specific fuel consumption increased. The concentrations of nitrogen oxides and carbon dioxide in the engine exhaust gas also slightly increased. At the same time, a clear reduction in average concentrations of carbon monoxide, hydrocarbons and particulates matter was obtained.